Externally validated predictive clinical model for untreated del(17p13.1) chronic lymphocytic leukemia patients. Issue 11 (12th October 2015) - Stephens, Deborah M.; Ruppert, Amy S.; Weirda, William G.; Jones, Jeffrey A.; Woyach, Jennifer A.; Maddocks, Kami; Jaglowski, Samantha M.; Andritsos, Leslie A.; Flynn, Joseph M.; Grever, Michael R.; Lozanski, Gerard; Tam, Constantine; et al.
<x xml:space="preserve">Abstract</x> Little is known about outcomes of patients with chronic lymphocytic leukemia (CLL) with del(17p13.1) karyotype at diagnosis. We reviewed 114 de novo del(17p13.1) CLL patients seen at our institution. Using proportional hazards models to identify pretreatment clinical variables significantly associated with treatment‐free survival (TFS) and overall survival (OS), we developed a simplified risk score for de novo del(17p13.1) CLL patients to predict TFS and OS based on these variables. These scores, particularly the very highest, can be utilized to identify high‐risk patients for expedient enrollment on clinical trials. Our data support careful observation for low‐risk patients, potentially preventing unnecessary use of aggressive therapies. Am. J. Hematol. 90:967–969, 2015. © 2015 Wiley Periodicals, Inc.